2020
DOI: 10.1002/da.23017
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of sexual functioning during treatment of MDD with adjunctive pimavanserin: A secondary analysis

Abstract: Background: Sexual dysfunction is common among patients with major depressive disorder (MDD). In the CLARITY study, the safety and efficacy of adjunctive pimavanserin, an inverse agonist at 5-HT 2A receptors, were demonstrated when added to existing treatment for MDD. This analysis provides a detailed assessment of the effects of pimavanserin on sexual function from the CLARITY study. Methods: Patients with a diagnosis of MDD in a depressive episode, inadequate response to ongoing antidepressant therapy, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
(34 reference statements)
2
5
0
Order By: Relevance
“…Sexual dysfunction is a common side effect of MAO inhibitors and selective serotonin uptake inhibitors (SSRI), and particularly problematic for women is the inability to have an orgasm. Pimavanserin augmentation of SSRI or serotonin and norepinephrine reuptake inhibitors (SNRI) in the CLARITY study had a substantial effect in improving sexual function in stage 1 among women [24]. As measured by the MGH-SFI, interest in sex, sexual arousal, ability to have an orgasm, and overall sexual satisfaction improved (p < 0.01, effect sizes of 0.56-0.75).…”
Section: Sexual Dysfunction As a Side Effect Of Ssrismentioning
confidence: 99%
“…Sexual dysfunction is a common side effect of MAO inhibitors and selective serotonin uptake inhibitors (SSRI), and particularly problematic for women is the inability to have an orgasm. Pimavanserin augmentation of SSRI or serotonin and norepinephrine reuptake inhibitors (SNRI) in the CLARITY study had a substantial effect in improving sexual function in stage 1 among women [24]. As measured by the MGH-SFI, interest in sex, sexual arousal, ability to have an orgasm, and overall sexual satisfaction improved (p < 0.01, effect sizes of 0.56-0.75).…”
Section: Sexual Dysfunction As a Side Effect Of Ssrismentioning
confidence: 99%
“…LS mean (95% CI) = −0.47 (−0.72, −0.22), p=0.0003)] 15. Furthermore, the authors found significant improvement with pimavanserin vs placebo in the sexual functioning as assessed with the single item (14th) of HAMD 15. …”
mentioning
confidence: 90%
“…35 Therefore, Freeman and colleagues undertook a secondary analysis of CLARITY data to evaluate the effect of pimavanserin on sexual functioning. 15…”
Section: Effect Of Pimavanserin On Symptoms Associated With Depressiomentioning
confidence: 99%
See 2 more Smart Citations